2014
DOI: 10.1186/1746-4269-10-49
|View full text |Cite
|
Sign up to set email alerts
|

Non-codified traditional medicine practices from Belgaum Region in Southern India: present scenario

Abstract: BackgroundTraditional medicine in India can be classified into codified (Ayurveda, Unani, Siddha, Homeopathy) and non-codified (folk medicine) systems. Both the systems contributing equally to the primary healthcare in India. The present study is aimed to understand the current scenario of medicinal practices of non-codified system of traditional medicine in Belgaum region, India.MethodsThe study has been conducted as a basic survey of identified non-codified traditional practitioners by convenience sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…2 Conventional and traditional medicines are also used widely as complementary or alternative medicines 3 , also to cure this deadly disease, surgical removal, chemotherapy and radiotherapy are most of the time not adequate or effective to overcome. 4 Traditional medicine system like Ayurveda, Siddha, Unani, Homeopathy and other systems (Folk practices) of medicine were based on most of plant derived medicines. In the large section of the population, plant based traditional systems of medicine playing a vital role to provide health care which increasing the over harvesting of natural products.…”
Section: Introductionmentioning
confidence: 99%
“…2 Conventional and traditional medicines are also used widely as complementary or alternative medicines 3 , also to cure this deadly disease, surgical removal, chemotherapy and radiotherapy are most of the time not adequate or effective to overcome. 4 Traditional medicine system like Ayurveda, Siddha, Unani, Homeopathy and other systems (Folk practices) of medicine were based on most of plant derived medicines. In the large section of the population, plant based traditional systems of medicine playing a vital role to provide health care which increasing the over harvesting of natural products.…”
Section: Introductionmentioning
confidence: 99%
“…While Ayurveda, Siddha, Unani, homeopathy, and allopathy have all been registered as ‘codified’ medical systems, there are also ‘non-codified’ medical systems. In South India, non-codified medical practitioners, called Vaidyas, have been recognized as playing central roles in community health in rural villages [ 16 ]. However, recent studies reported that the Vaidyas’ roles were decreasing because (1) codified medical systems were now available in many of rural villages, (2) rural people preferred to use allopathy rather than the Vaidya, and (3) Young people were not interested in learning non-codified medical systems, therefore there were less young Vaidyas [ 6 , 7 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants as folk medicines are extensively practiced in the rural zones of several developing countries [26,27]. Folk medicine practitioners claim that their medicine is inexpensive and more active than modern medicine [28]. The pharmacological actions of medicinal plant are due to the presence of multiple bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%